Ortnogonal-to-unitary ensemble crossover in the electronic specific heat of metal namoclusters: Статьи, посвященные столетию со дня рождения Л. В. Шубникова - Mukhin, S. I.; Kurapova, O. V.; Moiseev, I. I.; Vargaftik, M. N.; Volokitin, Y. E.; Mettes, F. L.; Jongh, L. J. de (ФІЗИКА НИЗЬКИХ ТЕМПЕРАТУР, 2001)
We present a theoretical and experimental study on the influence of a magnetic field on the energy-level statistics in metal nanoparticles. Based on the random-matrix theory, a gradual field-in-duced crossover behavior is predicted from the orthogonal to the unitary ensemble. Experimental data of the electronic specific heat of metal nanoparticles for different fields in the quantum-size temperature regime compare favourably with these theoretical (analytical) predictions.